Perception of Benefits and Barriers to Feeding in Relation to Stunting Incidence in Benua Community Health Center Area - Marsuki Marsuki; Tasnim Tasnim; Wa Ode Nova Noviyanti Rachman (Magister Kesehatan Universitas Mandala Waluya, 2026)
Introduction: Stunting remains a significant global public health problem, particularly impacting the physical growth and cognitive development of children under five. Indonesia, including Southeast Sulawesi Province, continues to face a high prevalence of stunting. In the Benua Community Health Center work area, more than 30% of children experience stunting, necessitating a behavioral-focused study. This is what drew researchers to investigate the Perception of Benefits and Barriers to Feeding in relation to Stunting in the Benua Community Health Center area. Method: This study uses a quantitative approach with a correlative analytical design and a cross-sectional model. The sampling technique uses cluster random sampling. The HBM constructs analyzed include perceived vulnerability, perceived seriousness, perceived benefits, and perceived barriers. Data were analyzed using the Chi-square test. Result: The analysis showed that there was no significant relationship between the incidence of stunting and the perception of obstacles (p = 0.367), but there was a significant relationship between the perception of seriousness and the incidence of stunting (p = 0.036). Conclusion: Perceived benefits and barriers to feeding are not associated with stunting. However, both factors have the potential to be protective, so education should focus on increasing maternal motivation by reinforcing the benefits of appropriate feeding practices and addressing the barriers encountered.